Digital repositories as memory areas and dissemination of Information - Almeida, Isledna Rodrigues de; Oliveira, Bernardina Maria J. F. de; Rosa, Maria Nilza Barbosa (Informação em Pauta, 2019)
Digital Repositories (RD) emerged in the context of the movement of free access to information, being a form of dissemination of knowledge production. Among the types of RD, there are the Institutional Digital Repositories (RDIs) that have become popular tools in academia for ensuring fast and practical access to quality scientific productions, associated with the institutional brand, ensuring institutional memory and still providing data for the services offered by academic social networks, ie, they are memorial spaces for information preservation. This article aims to conduct a desk research to collect information about RD, RDIs and Memory Space.